Substitute 2x-1 for y in the middle part, you get:
x^2 + x -6(2x-1) = 2x-1
This you can reduce to a quadratic equation for x.
2006-11-16 07:17:56
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
y = x^2 + x - 6 and y = 2x - 1
Substitute linear into quadratic to get:
x^2 + x - 6 = 2x - 1
Rearrange to get:
x^2 - x - 5 = 0
Complete the square:
(x-1/2)^2 - 21/4 = 0
x-1/2 = sqrt(21/4)
x = 1/2 + sqrt(21/4) and x = 1/2 - sqrt(21/4)
2006-11-16 19:32:59
·
answer #2
·
answered by martina_ie 3
·
0⤊
0⤋
Equate one to the other:
2x-1=x^2+x-6
Make it equalto zero:
x^2-x-5=0
No easy factorisation use quadratic formula:
a=1, b=-1, c=-5
(1 +/- SQROOT((1- (-20))))/2
=(1+/- SQR(21))/2
The answer would be a surd. If you are newto quadratics I would guess you have written the question wrong. If you are at GCSE/A Level standard then the answer would be a surd.
2006-11-16 15:36:30
·
answer #3
·
answered by Babak m 1
·
1⤊
0⤋
y=x^2 + x - 6y
=> x^2 + x = 7y ---(1)
x^2 + x - 6y = 2x - 1
=> x^2 + x - 6y - 2x + 1 = 0
=> x^2 - x +1 = 6y ---(2)
(1)x6, 6x^2 + 6x = 42y ---(3)
(2)x7, 7x^2 - 7x + 7 = 42y ---(4)
(4)-(3), x^2 - 13x + 7 = 0
x = [13 +- SQRT(169-4(1)(7))] / (2)(1)
x = [13 +- SQRT(141)] / 2
x = 12.4 or 0.563 (to 3 sig fig)
Substitute these values of x into any of the equations to find y.
2006-11-16 19:14:46
·
answer #4
·
answered by Kemmy 6
·
0⤊
0⤋
y=x^2 + x - 6y=2x - 1
for the moment, forgrt the y= part
x^2+x-6y=2x+1 subtract 2x-1
x^2-x+1-6y=0 since y=2x-1
x^2-x+1-6(2x-1)=0
x^2-13x +7=0
x=(13+/-â(169-28))/2=(13+/-â(141))/2
substitute this in y=2x-1 to find y
2006-11-16 15:22:48
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
y= x^2 + x - 6 ... (1)
y= 2x - 1 .......... (2)
Equation (1) - equation (2)
0 = x^2 - x - 5
So x = ½(1 ± â41) by the quadratic formula
When x = ½(1 + â41)
y = â41
and when x = ½(1 - â41)
y = - â41
2006-11-16 15:25:54
·
answer #6
·
answered by Wal C 6
·
2⤊
0⤋
Y = X^2 - x - 6y + 1 = 0
Y + 6Y = X^2 - x + 1
SO Y = X^2 - x + 1 all over 7.
2006-11-16 15:18:31
·
answer #7
·
answered by Galaxy D 2
·
0⤊
1⤋
y=x^2+x-6......(1)
y=2x-1
......x=(y+1)/2.......(2)
substitute for x into (1)
y=((y+1)/2)^2+(y+1)/2-6
4y=y^2+2y+1+2y+2-24
y^2=21
>>>>>y=+or- sqrt21
from(2),
when y= +sqrt21
x=(sqrt21+(1))/2
when y= -sqrt21
x=(1-sqrt21)/2
1 hope that this helps
2006-11-16 17:44:06
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
You sure you have the question write? Simultaneous equations should have two distinct equations
2006-11-16 15:19:44
·
answer #9
·
answered by Jomtien C 4
·
0⤊
0⤋
x^2 -x+1=7y
(x^2-x+1)/7=y
((1/7)+- sqr (1/7)^2 -4*(1/7)*(1/7))7 solve that for your answer
2006-11-16 15:19:58
·
answer #10
·
answered by dimachevelle 2
·
0⤊
1⤋